Professional Negligence, Mismanagement and Malpractice. Polish Companies in the Light of Supreme Audit Office Materials in the Years 1976-1980 - Lesiakowski, Krzysztof (Studia Historiae Oeconomicae, 2016)
The birth of the “Solidarity” Independent Self-governing Trade Union in 1980 was accompanied by a strong revisionist movement. The Polish society expected punishment for the previous administration, led by Edward Gierek, as it was their policy up to that point that resulted with enormous external debt and ubiquitous shortages of consumer goods. A lot was said about wastefulness, corruption and professional negligence, both in the state administration and in the managements of Polish companies. And these opinions were somehow justified, as evidenced by the results of audits performed by the Supreme Audit Office (Najwyższa Izba Kontroli, NIK) in the years 1976–1980. Information recorded in the audit documentation was in line with the social attitudes. Due to formal and legal conditions back then, NIK auditors could not inspect the most important companies, however they managed to prove that the scale of illegal actions committed by directors and managers was large and increased year by year.